"We always felt psychologically unstable": A qualitative study of midwives' experiences in providing maternity care during the COVID‐19 pandemic in Tanzania - Angelina A. Joho; Subira Abdallah (Wiley, 2024)
Abstract Aim We explored midwives' experiences and challenges in providing maternity care during the period of the first surge of the COVID‐19 pandemic in Dodoma. Design Phenomenological study design was used to explore midwives' experiences and challenges in providing maternity care during the COVID‐19 pandemic in Tanzania. Methods We conducted interviews with a total of 23 midwives, using semi‐structured interviews and an audio recorder. Five focus group discussions (FGDs) were conducted. To analyse the data, we used interpretive phenomenological thematic data analysis with NVivo software. To analyse templates, we followed a step‐by‐step process, starting with familiarizing ourselves with the data, followed by preliminary coding, organizing themes, developing an initial coding template, using the initial template, refining the template and finally applying it to the entire dataset. Results It was found that three themes and eight subthemes merged in the current study. The main themes were ① mental health distress, ② work environment challenges and ③ isolation of midwives by different groups. Public Contribution Reducing risk and protecting midwives from infectious diseases will improve the workforce, reduce the number of hospital stays, reduce the cost of hospital services, improve birth outcomes and indirectly improve family, community and national economies. Conclusion Due to the system's failure to provide psychological support, protective environment and isolation rooms for confirmed or suspected cases put midwives at a higher risk of contracting the virus and had to work in a stressful environment. In addition to having the right tools, midwives must also receive emotional and psychological support in order to be at their best. The system must ensure that midwives are ready for uncertain times, such as pandemic infectious disease outbreaks, by providing protective work place environment such as personal protective equipment, psychological support and isolation room for confirmed COVID‐19 cases.